Nutritional Supplementation in the Elderly Population: A Review Study - Asma Alraes,; Khayriyah Alriqeee,; Hager Abugrain,; Abuagela, Manal; Boshra Bensaud,; Hanin Doggah,; Fatma Gwili, (AlQalam Journal of Medical and Applied Sciences, 2025)
The global demographic shift towards an aging population presents significant challenges in nutritional health for older adults. This review discusses the current research revealing the role of dietary supplements in addressing common nutrient deficiencies and supporting the health of the elderly. As the number of individuals aged 60 and older is expected to double by 2050, understanding the impact of age-related physiological changes on nutrition is crucial. Elderly individuals face an increased risk of nutrient deficiencies due to decreased appetite, impaired absorption, and chronic health conditions. Key deficiencies often observed include calcium, vitamin D, zinc, iron, vitamin B, and omega-3 fatty acids. These deficiencies are critical for bone health, immune function, cognitive abilities, and muscle maintenance. This review evaluates evidence from peer-reviewed studies and clinical trials, highlighting the efficacy and safety of various supplements in mitigating these deficiencies. Additionally, it explores the role of dietitians in managing nutritional care for the elderly, emphasizing the need for personalized dietary strategies. The findings underscore the importance of targeted nutritional interventions and supplementation to enhance the aging population’s well-being and quality of life.